Fiscal Rules in the European Union: Goals, Evolution, Results - Anatoly V. Kholopov (Современная Европа)
Common fiscal rules are necessary in the EU to avert cross-border negative spillovers from national fiscal policies and to maintain financial stability and confidence in the single currency. The EU fiscal rules have undergone numerous reforms and over time they have become very complex. While fiscal rules have had some impact in constraining deficits, they did not prevent the euro area debt crisis and the rise in debt ratios. The main reason for the low effectiveness of fiscal rules was poor compliance. On average budgetary policies of the EU member states were compliant with fiscal rules in just over half of the cases. The main points of rules' critique were their procyclicality, negative growth impact, excessive complexity, insufficient transparency and weak enforcement. Many countries have broken the rules without facing sanctions. After the suspension of the rules during the COVID-19 pandemic, the Council in April 2024 approved new fiscal rules. The key changes in the rules are: the adoption of a differentiated approach towards each member state, the usage of single operational indicator – net primary expenditure, setting a reference trajectory for countries that do not comply with the rules, and the encouragement of reforms and investment in key domains. The new rules have retained a number of weaknesses of the old rules and have received an ambiguous assessment from expert community.